Comparative physical activity as a global question to assess physical activity among university students - Diehl, Katharina; Brassat, Alessia; Hilger-Kolb, Jennifer (BMC sports science, medicine & rehabilitation, 2021)
Background: To assess physical activity (PA), a comparative measurement - evaluating one’s own PA compared to others - may be an appropriate method. In previous studies, the use of comparative measurements led to an effect known as unrealistic comparative optimism (UCO) - people being unrealistically optimistic about their behavior. Our aim was to use this comparative measurement in university students to quantify the prevalence of UCO at the group level and to draw conclusions on its validity. Methods: We used data from the Nutrition and Physical Activity in Adolescence Study (NuPhA), a cross-sectional online survey that included only self-reports (n = 689). To assess PA among students, they were asked to rate their PA level compared to that of their same-aged fellow students. In addition, we used the Godin-Shephard leisuretime PA questionnaire and other questions on PA for comparisons. We used bivariate and cluster-based analyses to identify potential UCO. Results: We found that UCO at the group level led to an uneven distribution, with a higher proportion of students who rated themselves as being more physically active than average. However, the individual assessment of PA with a single and simple comparative question seemed to be valid. Discussion: A global single comparative question seems useful for studies where PA is measured as a covariate in university students.